Effects of Different Strategies on High Thrombus Burden in Patients with ST-Elevation Myocardial Infarction Undergoing Primary Percutaneous Coronary Catheterization - Nasrullah, Aftab Ahmed Solangi, Amir Jamil, Khalid, Muhammad Tahir, Zahirullah, (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: The aim of this study is to evaluate the impact of thrombus aspiration and intracoronary-targeted thrombolysis on myocardial perfusion. The study also analyses the effect of different technological approaches on ST-elevation myocardial infarction (STEMI) patients undergoing primary percutaneous catheterization (IMR and SPECT). Study Design: Randomized control trial Place and Duration: Cardiology Department of Punjab institute of cardiology Lahore from September 2021 to September 2022. Methodology: Sixty six STEMI patients of either gender were enrolled in this study. Detailed demographics were recorded after taking informed written consent. All the patients were equally divided into two groups (TA and IT group) 33 patients in each group. Blood samples from the venous veins were collected for routine laboratory examinations, biochemical tests included blood sugar test, lipid profile test, C reactive protein test, liver and kidney function tests, myocardial indicators as troponin I and blood tests for other organs. Vital sign changes and intracoronary thrombolysis were investigated intensively when the drug was injected. Additionally, patients in the TA group would get an extra 5 or 10mg of Pro-UK if there was a residual thrombus and they had repeated thrombus aspirations utilizing Export AP. SPSS software 24.0 was used for the data analysis. Results: The analysis showed that the IT group has greater values of thrombus burden, TIMI myocardial perfusion %, and TIMI frame count. The statistical analysis revealed that during the 90-day follow-up, there is no change in MACEs or heart function was observed. The values of 12-month follow-up illustrated that there is significant differences in the infarct size assessed by SPECT, the left ventricular ejection fraction evaluated by echocardiography, and the composite MACEs between the 2 groups (P=0.034). Conclusion: Effective therapies include intracoronary-targeted thrombolysis and thrombus aspiration and safe ways to treat STEMI patients with an increased coronary thrombus burden. Keywords: ST-Elevation Myocardial Infarction, Primary Percutaneous Coronary Catheterization, Thrombus Aspiration, Thrombolysis